Potential of Portable Hydrokinetic Energy Turbine Design for Remote Communities in Sarawak - Jamaluddin, Z.Z.; Azrulhisham, E.A.; Azri, M.A.; Norazwani, Muhammad Zain,; Saiful Bahari, Bin Hj Mohd Yusoff (Institute of Advanced Scientific Research, 2018)
- The Hydro kinetic energy turbine is rescuer technology for power supply to replace energy from fossil fuel in small remote communities. This technology is used in rivers that are not high and are off gird electric power production. The portable hydro kinetic flotation method is used for convenience of communities altering location position to a suitable place for use. The Cross flow turbine method and 200w electric power production is suitable for small remote communities in Sarawak. The length of turbine diameter has been determined based on the planted data that has been taken at the inland rivers. Aspects of portable, floating and material aspects should also be taken into account. The portable kinetic hydro concept is designed for the next prototype process. This paper enhances new technologies and prospects, challenges and the new framework for adaptation in remote hydrological settings.